Strategi Adaptif Untuk UMKM di Sukabumi Menghadapi Tantangan Supply Chain - Novia Ramadhani, Luna; Hapsari, Hera Siti (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
MSMEs in Sukabumi have a significant role in the local economy but are faced with supply chain challenges, including resource limitations, demand fluctuations, and market uncertainty. This study uses a qualitative approach to analyze the adaptive strategies implemented by five local MSMEs. The findings show that supplier diversification, the utilization of digital technologies such as e-commerce and cloud-based stock management, and product innovation play an important role in improving operational efficiency and competitiveness. This research also reveals the need for collaboration with stakeholders to deal with resource limitations. The results provide practical recommendations for MSMEs as well as contribute to the development of policies that support the sustainability of their businesses.